KINERJA BAURAN PEMASARAN JASA PENDIDIKAN TERHADAP KEPUTUSAN MAHASISWA MEMILIH DAN WOM (WORD OF MOUTH) SEBAGAI MODERATING VARIABLE PADA MAHASISWA AKADEMI KEBIDANAN SALMA DI KABUPATEN SIAK - Ervinawati, Imran, (Menara Ilmu, 2019)
This research aims to analyze performance of educational services marketing mixtowards student’s choices decision, and word of mouth communication on Salma’smidwifery academy students at Siak regency.The number of research samples are all students, 85 by census method. Then, datascollecting through questionnaires direct spreading by using a Likert scale. Analytical datasmethod in this research using two stages regression through reliable statistical measuredby SPSS version 20 software.Research result shows that independent variables, educational services marketingmix which consist of product, promotion, place, people, process, and physical evidencehaving significant influence and positive towards student’s choices decision, except pricevariable which having no significant influence, only positive, and WOM (Word of Mouth)communication having significant influence and positive towards relation of student’schoices decision, and marketing mix, means WOM (Word of Mouth) communication whichwas effect of best higher education services value is expected to intensify studentpreference to study at Salma’s midwifery academy.Keywords : Educational Services Marketing Mix, Student’s Choices Decision, Word ofMouth.